Criminal Legislation on Responsibility for Production, Storage, Carriage or Sale of Goods and Products, Fulfillment of Works or Rendering of Services, Which Do Not Meet Safety Standards: Improvement and Practice - SUKHANOV, Alexandre V.; KIRILENKO, Victoria S.; PRATSKO, Gennady S. (Journal of Advanced Research in Law and Economics, 2017)
The authors conduct a scientific theoretical and practical study of the criminal responsibility for production, storage, carriage or sale of goods and products, fulfillment of works or rendering of services, which do not meet safety standards. The study aims at systematizing the criminal jurisprudence in terms of the formal elements of the defined crime. There are conclusions, elaborated recommendations and legislative proposals that significantly reduce some investigative and legal errors related to qualifying such acts. The article also suggests options for increasing the practical effectiveness of Chapter 238 of the Criminal Code of the Russian Federation.